Advances in research on anthropogenic drivers of climate change - JORGENSON, Andrew (Institutional Knowledge at Singapore Management University, 2024)
This chapter provides an overview of advances in social science research on the anthropogenic drivers of climate change. Anthropogenic drivers refer to the social systems and human actions causing GHG emissions, and societal factors shaping and conditioning those actions. The authors summarize the contemporary drivers research literature on (1) economic growth, (2) income and wealth inequality, (3) environmental load displacement and ecologically unequal exchange, (4) militarization, and (5) corporations. In addition to summarizing recent work, the authors identify future directions for each of these areas of research, as well as ways in which they can be better integrated.